Temporal lobe epilepsy surgery: Piriform cortex resection impacts seizure control in the long‐term. Issue 8 (1st July 2022) - Borger, Valeri; Hamed, Motaz; Bahna, Majd; Rácz, Áttila; Ilic, Inja; Potthoff, Anna‐Laura; Baumgartner, Tobias; Rüber, Theodor; Becker, Albert; Radbruch, Alexander; Mormann, Florian; Surges, Rainer; et al.
Abstract: Objective: Recently, we showed that resection of at least 27% of the temporal part of piriform cortex (PiC) strongly correlated with seizure freedom 1 year following selective amygdalo‐hippocampectomy (tsSAHE) in patients with mesial temporal lobe epilepsy (mTLE). However, the impact of PiC resection on long‐term seizure outcome following tsSAHE is currently unknown. The aim of this study was to evaluate the impact of PiC resection on long‐term seizure outcome in patients with mTLE treated with tsSAHE. Methods: Between 2012 and 2017, 64 patients were included in the retrospective analysis. Long‐term follow‐up (FU) was defined as at least 2 years postoperatively. Seizure outcome was assessed according to the International League against Epilepsy (ILAE). The resected proportions of hippocampus, amygdala, and PiC were volumetrically assessed. Results: The mean FU duration was 3.75 ± 1.61 years. Patients with ILAE class 1 revealed a significantly larger median proportion of resected PiC compared to patients with ILAE class 2–6 [46% (IQR 31–57) vs. 16% (IQR 6–38), p  = 0.001]. Resected proportions of hippocampus and amygdala did not significantly differ for these groups. Among those patients with at least 27% resected proportion of PiC, there were significantly more patients with seizure freedom compared to the patients with <27% resected proportion of PiC (83% vs. 39%, p  = 0.0007). Conclusions: Our results show a strong impact of the extent of PiC resection on long‐term seizure outcome following tsSAHE in mTLE. The authors suggest the PiC to constitute a key target volume in tsSAHE to achieve seizure freedom in the long term.